2015
DOI: 10.1016/j.jrras.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Improving the nutritional value of canola seed by gamma irradiation

Abstract: a b s t r a c t This investigation aims to evaluate the effects of g-irradiation on anti-nutritional factors, in-vitro protein digestibility and functional properties of canola meal protein, physicochemical properties and fatty acid composition of canola seed oil. Irradiation at doses 10, 20, 30 KGy had no effects on the chemical composition of canola seed, while decreased the total glucosinolate content by 15.6, 30.4 and 49.4%; and phytic acid by 29, 55 and 100%, respectively. On contrary, in-vitro protein di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
(26 reference statements)
2
17
0
Order By: Relevance
“…Similar trends, but somewhat to higher extents, were noticed in plants irrigated with wastewater. These results agree with Anwar et al (2015), who found that γ-irradiated is a safe and successful method to improve the nutritional value of canola seeds as well as the functional properties of its proteins. This might occur because of the significant increases that took place in plant roots owing to seed irradiation; consequently, N-uptake increased during the early stages (Bouchet et al 2016).…”
Section: Nitrogen Uptakesupporting
confidence: 92%
“…Similar trends, but somewhat to higher extents, were noticed in plants irrigated with wastewater. These results agree with Anwar et al (2015), who found that γ-irradiated is a safe and successful method to improve the nutritional value of canola seeds as well as the functional properties of its proteins. This might occur because of the significant increases that took place in plant roots owing to seed irradiation; consequently, N-uptake increased during the early stages (Bouchet et al 2016).…”
Section: Nitrogen Uptakesupporting
confidence: 92%
“…Seed biochemical composition, and consequently the resources available for the seed-associated microbiota could also explain differences among crops (Sliwinska and Bewley 2014;Torres-Cortés et al 2019). T. aestivum and L. culinaris seeds are rich in carbohydrates and proteins, whereas B. napus is rich in oil and other compounds including glucosinolates, phytates, and phenols (Shewry and Halford 2002;Anwar et al 2015;United States Department of Agriculture-Nutrient Database 2019). Generation explained 10% and 15% of the variance in bacterial and fungal seed microbiomes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, monoacylquinic acids are the major compounds, consisting of bound caffeic and p -coumaric acids [ 127 ], which can be hydrolysed into their corresponding acids. Therefore, the free phenolic acids (gallic, sinapic, protocatechuic) were found in high concentrations only in canola seeds (52 mg/g defatted material, or up to 31 mg/g dry weight) [ 129 , 130 ]. Therefore, the seeds (sunflower seeds, chia) extracts contain the isomers of phenolic acids ( cis - and tran s-ferulic acids, and p -, o -, m -coumaric acids) [ 107 , 127 ].…”
Section: Production and Extraction Of Phenolic Acids From Plants Amentioning
confidence: 99%